Head-to-Head Comparison of UHPLC-MS/MS and Alinity C for Plasma Analysis of Risperidone and Paliperidone - Francisco José Toja-Camba; Gonzalo Hermelo-Vidal; Carolina Feitosa-Medeiros; María Vidal-Millares; María José Durán-Maseda; Anxo Fernández-Ferreiro; Cristina Mondelo-García (Pharmaceuticals)
Background and objectives: Risperidone, a second-generation antipsychotic widely used in the treatment of schizophrenia, requires therapeutic drug monitoring due to its high interindividual variability. UHPLC-MS/MS is considered the gold standard for pharmacokinetic studies owing to its superior sensitivity and specificity, although it involves time-consuming manual sample preparation. In contrast, the Alinity C system, fully automated, simplifies sample processing, but only measures the active moiety (risperidone plus paliperidone). The aim of this study is to compare the performance of UHPLC-MS/MS and the Alinity C system for the determination of risperidone and paliperidone concentrations in plasma. Methods: A total of 115 plasma samples of 115 patients, 92 and 23 under risperidone and paliperidone long-acting treatment, respectively, were analyzed using both methods. Results: A strong correlation for the active moiety (risperidone plus 9-OH-Risperidone) (rs = 0.95) was observed. However, Bland–Altman analysis revealed a mean bias of 0.996 ng/mL, indicating that the Alinity C system slightly overestimates concentrations compared to UHPLC-MS/MS. While there was substantial agreement between methods (κ = 0.72), discrepancies were observed in 16.3% of cases, which could impact clinical decision-making. When analyzing paliperidone separately, the agreement was lower (κ = 0.63), with greater variability observed. Conclusions: These findings suggest that, while the Alinity C system is suitable for routine therapeutic monitoring, UHPLC-MS/MS remains the preferred method in clinical scenarios requiring higher precision, particularly for patients with concentrations near therapeutic thresholds.